Profile Of Congenital Heart Disease (CHD) Patients In Cirebon, Indonesia: Maternal Passive Smoking Risk : Maternal Passive Smoking Risk - Pratiwi, Witri; Puji Rachmawan, Yogi (STIKes Mandala Waluya Kendari, 2024)
Background: Congenital heart disease (CHD) is the most common congenital disorder and a leading cause of infant mortality. Maternal pregnancy history is considered a potential risk factor for CHD. This cross-sectional study aimed to investigate the patient and maternal profile of CHD cases in Cirebon, Indonesia. Methods: The study was conducted at Hasna Medika Cardiovascular Hospital from November 2019 to March 2020, and data were collected through questionnaires and medical records. The study included 28 CHD patients, of whom 57.1% were female, and most had acyanotic CHD (82.1%). Results: None of the mothers had a history of active smoking, but all were exposed to passive smoking. Additionally, 17.9% of the samples had a history of fever during the first trimester, 17.9% took medication during pregnancy, and all consumed vitamins and supplements. Hormonal contraceptive failure accounted for 17.9% of CHD cases, while 7.1% of mothers had gestational hypertension. None of the mothers had gestational diabetes mellitus. Conclusions: The study suggests that passive smoking may be closely related to CHD, but further research is needed to confirm this association. Therefore, it is crucial for pregnant women to avoid exposure to cigarette smoke. Health promotion programs that educate the public about the risks of smoking during pregnancy and infancy are highly encouraged.